Novel soda lignin/PLA/EPO biocomposite: a promising and sustainable material for 3D printing filament - Anuar, Hazleen; Abd Rahman, Nurul Amirah; Manshor, Mohd Romainor; Alli, Yakubu Adekunle; Alimi, Oyekunle Azeez; Alif, Fathilah; Suhr, Jonghwan (Elsevier, 2023)
Polylactic acid (PLA) has been extensively used in 3D printing due to its low melting temperature and minimal warping. This study investigated the reinforcement of PLA filament with soda lignin from oil palm empty fruit bunches (OPEFB) in the presence of epoxidised palm oil (EPO) as 3D printable filament. The alkaline extraction method was carried out used sodium hydroxide (NaOH), followed by precipitation with mineral acids utilising one-factor-at-a-time (OFAT). The highest extraction yield was 30 % using 1 M NaOH and 20 % phosphoric acid. Fourier transforms infra-red (FTIR) confirmed the removal of lignin in the absence of 1740 cm⁻1 and 1513 cm⁻1 peaks. Scanning electron microscopy images revealed rough surface and less voids observed at the cross-section of filament. The addition of 1 phr lignin and 5 phr EPO (PLAE1) showed improvement in thermal and mechanical properties, with higher Tₒ around 5 °C and 10 % crystallinity. Brittleness is reduced by 5 % for PLAE1 compared to unfilled PLA due to increase of elongation at break. Rheology analysis revealed that PLA/lignin filament appeared to be more viscous, shown by lower complex viscosity of roughly 100 Pa compared to 800 Pa for PLA at 1 rad/s. PLAE1 exhibiting decreased in brittleness by 4 %, and high impact strength of 37 %. Dynamic mechanical analysis revealed that PLAE1 had lower rigidity than unfilled PLA with lower damping factor and storage modulus of 1.67 and 1.54 GPa. The findings revealed that the PLAE1 biocomposite has potential as alternative filament for sustainable 3D printing.